Dadih Susu Sapi Hasil Fermentasi Berbagai Starter Bakteri Probiotik yang Disimpan pada Suhu Rendah: Karakteristik Kimiawi - E Taufik (Faculty of Animal Science, Bogor Agricultural University, 2004)
This experiment was designed to improve quality of dadih in a process which was more controlled. The use of cow milk was to replace buffalo milk utilization due to its availability was very limited; the use of probiotic starter combination was to conduct fermentation process of dadih more controlled, and the specific characteristics of dadih could be measured. Therefore the aim of this experiment was to evaluate the best starter concentration that will be used in fermentation process of dadih and to investigate chemical characteristics of dadih from cow milk fermented with different combination of probiotic starter bacteria (L. plantarum (A1), L. plantarum + L. acidophilus (A2), L. plantarum + B. bifidum (A3) and L. plantarum + L. acidophilus + B. bifidum (A4)) and stored at low temperatures for 0, 7 and 14 days. The results showed that the best starter concentration was 3% with similar comparison among starters and the combinations of probiotic starter bacteria did not affect significantly moisture, protein, fat, ash contents, pH and titratable acidity of dadih at H-0 (before storage). The characteristics of dadih after storing for 14 days at low temperature showed that combinations of starter affected significantly pH and titratable acidity (P